Organic Lawn Care - Laurie E. Trenholm (EDIS, 2003)
There is a renewed interest today in organic lawn care and a trend among many homeowners to consider long-term environmental concerns in their lawn maintenance programs. The term "organic" can cover many different aspects of lawn care, including fertility and pest management. There is also a certain amount of confusion and misunderstanding over the concept of organic lawn care and what it entails, and as to whether products are beneficial or fall into the “snake oil” category. This document is ENH883, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 29, 2003.